Religion and tourism : crossroads, destinations and encounters - Stausberg, Michael (Routledge, 2011)
This book explores the dynamic interaction between religion and tourism in the modern world. It considers questions such as:do travellers leave their religion at home when they are touring - and what happens if not? what are the relationships between tourism and pilgrimage?what happens to religious performances, places and festivals that function as tourism attractions? Other chapters examine religious theme parks, wellness and spa tourism, the roles played by tourist guides, guidebooks and religious souvenirs, and the role of tourism as a major.